2018
DOI: 10.1021/acs.est.8b02381
|View full text |Cite
|
Sign up to set email alerts
|

Size-Resolved Surface-Active Substances of Atmospheric Aerosol: Reconsideration of the Impact on Cloud Droplet Formation

Abstract: Our current understanding of the importance of surface-active substances (SAS) on atmospheric aerosol cloud-forming efficiency is limited, as explicit data on the content of size-resolved ambient aerosol SAS, which are responsible for lowering the surface tension (σ) of activating droplets, are not available. We report on the first data comprising seasonal variability of size-segregated SAS concentrations in ambient aerosol particulate matter (PM). To assess the impact of SAS distribution within PM on cloud dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 63 publications
3
42
0
Order By: Relevance
“…Gérard et al (7,29) recently reported total surfactant concentrations in collected ambient fine aerosol reaching several tens to hundreds millimolar across Europe. Moreover, surfactant concentrations are enhanced in smaller (<200-nm diameter) atmospheric particles (46). Such atmospheric observations combined with our results suggest surfactants in some cases will substantially impact the activation of atmospheric particles into cloud droplets.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Gérard et al (7,29) recently reported total surfactant concentrations in collected ambient fine aerosol reaching several tens to hundreds millimolar across Europe. Moreover, surfactant concentrations are enhanced in smaller (<200-nm diameter) atmospheric particles (46). Such atmospheric observations combined with our results suggest surfactants in some cases will substantially impact the activation of atmospheric particles into cloud droplets.…”
Section: Discussionsupporting
confidence: 74%
“…The surface monolayer model predictions suggest surfactant concentrations on the order of several tens to 100 mM, consistent with reported atmospheric concentrations, are required to substantially affect N d (i.e., modify SS c by >20%). These predictions highlight the necessity of a more comprehensive understanding of the types and concentrations of surfactants in aerosol, as to date only a few studies in a few environments have been reported (7,8,10,29,46,47). Global simulations of N d have only rarely incorporated such surface partitioning models (5,6), in part because partitioning effects had not been experimentally confirmed until this work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous paper of Frka et al [36], a broad voltammetric peak that was recorded around a potential of −0.70 V in continental, coastal, and urban aerosol samples as well as in the isolated atmospheric HULIS, could be possibly associated with the presence of RSS. These RSS contribute to the surfactant activity, since HULIS material, i.e., HULIS concentration can be regarded as a rough upper-limit estimate of aerosol water-soluble SAS [53]. Moreover, RSS are an important part of the total S pool in aerosol samples.…”
Section: Electrochemical Rss Responses In Ws Fraction Of Fine Marine mentioning
confidence: 99%
“…Phase sensitive alternating current (AC) voltammetry was applied for SAS analysis, being already used as a successful tool for the determination of SAS in a plethora of environmental aquatic samples (Frka, et al 2009;Frka, et al 2012;Kroflič, et al 2018). Measurements (outof-phase mode, frequency 77 Hz, and amplitude 10 mV) were performed with μAutolab-type II (Eco Chemie B. V., The Netherlands), GPES 4.6 software (Eco Chemie B. V., The Netherlands), followed the method of Ćosović and Vojvodić (1998) Gašparović, et al 2017).…”
Section: Sas Analysismentioning
confidence: 99%